FORMULASI DAN UJI EFEKTIVITAS SEDIAAN GEL EKSTRAK ETANOL DAUN SAMBUNG RAMBAT (Mikhania mikrantha) SEBAGAI ANTIINFLAMASI PADA TIKUS PUTIH JANTAN - Harahap, Nurul Dahlia (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Background: Inflammation is a normal response due to the immune to eliminate pathogens, prevent the spread of tissue damage and repair damaged tissue due to pathological symptoms of a disease, Objective: To determine the concentration that provides effectiveness as an anti-inflammatory against male white rats induced with 1% carrageenan. . Methods: The vines were extracted using 96% ethanol as a solvent. 15 wistar rats were adapted for seven days. The rats were randomly divided into 5 groups. Group I (negative control) based on gel, group II (positive control) voltaren gel, group III ethanolic extract of vines with a concentration of 5%, group IV of ethanolic extract of vines of leaves 10%, group V of ethanolic extract of vines of leaves 15%. All treatment groups were sublanted with 1% carrageenan. Edema in rat feet was measured at 30 minutes to 180 minutes. Data analysis used the one way ANOVA method. Results: from the result of the study show that each treatment group experienced a reduction in inflamasi,in the 5 treatment groups, the best reduction in inflmation was the consentration 15% wich was the best compared to voltaren gel in reducing inflamation,Conclusion: the ethanolic extract of vines has an almost equeval__ent effect the drug voltaren but the drug voltaren is more effegtive reducing inflamation.